1984
DOI: 10.1111/j.1365-2478.1984.tb00742.x
|View full text |Cite
|
Sign up to set email alerts
|

THREE‐TERM TAYLOR SERIES FOR t2x2‐CURVES OF P‐ AND S‐WAVES OVER LAYERED TRANSVERSELY ISOTROPIC GROUND*

Abstract: The arrival‐time curve of a reflection from a horizontal interface, beneath a homogeneous isotropic layer, is a hyperbola in the x ‐ t‐domain. If the subsurface is one‐dimensionally inhomogeneous (horizontally layered), or if some or all of the layers are transversely isotropic with vertical axis of symmetry, the statement is no longer strictly true, though the arrival‐time curves are still hyperbola‐like. In the case of transverse isotropy, however, classical interpretation of these curves fails. Interval vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 14 publications
0
92
0
1
Order By: Relevance
“…For example, in the case of isotropy or elliptical anisotropy, the reflection moveout is hyperbolic (A 4 = 0). For VTI symmetry, equation (6) reduces to the known azimuthally independent quartic coefficient A 4 given by Hake et al (1984) and Tsvankin and Thomsen (1994). In the case of a horizontal HTI layer, with a horizontal symmetry axis parallel to x 1 of the (x 1 ,x 3 ) plane, the components A …”
Section: Nhmo Coefficient Amentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in the case of isotropy or elliptical anisotropy, the reflection moveout is hyperbolic (A 4 = 0). For VTI symmetry, equation (6) reduces to the known azimuthally independent quartic coefficient A 4 given by Hake et al (1984) and Tsvankin and Thomsen (1994). In the case of a horizontal HTI layer, with a horizontal symmetry axis parallel to x 1 of the (x 1 ,x 3 ) plane, the components A …”
Section: Nhmo Coefficient Amentioning
confidence: 99%
“…On conventional-length spreads (spreadlength-to-depth ratio ≤ 1), the hyperbolic moveout equation (1) can be expected to provide an adequate description of the moveout, but the NMO velocity should be averaged over the stack of layers. In isotropic and VTI media, this averaging is performed by means of the conventional isotropic Dix (1955) equation (Hake et al, 1984). Furthermore, Alkhalifah and Tsvankin (1995) showed that the Dix equation remains valid in symmetry planes of any anisotropic medium, if the interval NMO velocities are evaluated at the ray-parameter value of the zerooffset ray.…”
Section: Moveout In Multilayered Mediamentioning
confidence: 99%
See 3 more Smart Citations